Improving Academic Self Efficacy in Reducing First Year Student Academic Stress - Ade Herdian Putra; Riska Ahmad (Universitas Negeri Padang, 2020)
The difference between academic demands in college and high school requires that first-year students must be able to adjust. When meeting academic demands in college, first-year students can experience academic stress. Academic stress can interfere with first-year students in meeting the academic demands of higher education. One of the factors that influence academic stress is academic self efficacy. Therefore, to reduce academic stress experienced by first-year students can be done by increasing academic self-efficacy. This article is a literature study that will explain about increasing academic self efficacy in reducing the academic stress of first year students. Hopefully this article can be a reference.